Dilemmas of family businesses financing by private equity - Węcławski, Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Purposes of conducting family businesses are specific. Striving for survival and ensuring succession causes an aversion to risk and caution when undertaking development projects. Such an attitude is associated with capital structure that prefers internal financing sources. In the event of external financing foreign capital would be used in the first place. Family businesses rarely use private equity financing. A relatively lower risk for for their independence is related to mezzanine capital. Venture capital consitutes a threat of takeover. Private equity is convenient for ownership changes, especially for succession.